Adaptive Kanban control systems for two-stage production lines. (6th May 2010) - Takahashi, Katsuhiko; Morikawa, Katsumi; Hirotani, Daisuke; Yoshikawa, Takeshi
To respond to demands while reducing inventories, the Kanban control system (KCS) has been developed as a typical system for just-in-time production system. The original KCS has been revised to adaptive KCS by Tardif and Maaseidvaag (2001). However, in the adaptive KCS, how to adjust the number of Kanbans at each stage has never been considered. This paper proposes two types of adaptive KCS for two-stage production lines according to the difference of adjusting the number of Kanbans at each stage. A queuing-network model of the two types of adaptive KCSs is developed, and the performance is analysed and compared with each other by using Markov analysis. Numerical calculations are conducted to investigate the influence of the processing rate and cost parameters on the performance measures. The results show the advantages of each system over the other.